Fonética e fonologia na escola: de enfoques restritos a possibilidades amplas - Silva, Ione Batista da (2021)
This studyhas presented as an object of study, contents related to phonetics and phonology, inserted in the high school pedagogical practices. Itsmain objective is to support the teaching work related to these contents. It is based on theoretical contributions with phoneticphonological approaches (Câmara Jr., 1972;1999; Cagliari, 1999; 2005; Cristófaro-Silva, 2003) and sociolinguistic ones(Bagno,2008). It has been developed on two methodological fronts: the first, analytical-descriptive, which has focused on the Portuguese language textbook, Esferas das línguas, by the authors,Maria Inês Batista Campos and Nívia Assumpção, from 2018 to 2021, in the 1st series High School at the State School Professor Tertuliano Pinheiro Filho, in Barcelona-RN; and the second, with a propositional bias, which has configured the composition of an activity notebook. The research has pointed out, on the one hand, the absence or little depth of approaches related to phonetics and phonology in the analyzed textbook; and, on the other hand, it has proposed a notebook of activities that aims to supplement, with regard to this gap, the teacher's pedagogical practice in high school.